If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+n-3+3=3+n
We move all terms to the left:
3+n-3+3-(3+n)=0
We add all the numbers together, and all the variables
n-(n+3)+3-3+3=0
We add all the numbers together, and all the variables
n-(n+3)+3=0
We get rid of parentheses
n-n-3+3=0
We add all the numbers together, and all the variables
=0
n=0/1
n=0
| P/2+5p+6=0 | | p-5=-1+2p-3p-12 | | 7x+3+3x-7=-24 | | 7-8(n+7)=-81 | | 2x+6/3-8=10 | | 175=3+4(1-6n) | | 6×+5y=11 | | -3x-7x=-10 | | N=1/6;4/n | | 0=-0.055x^2+116x-5280 | | Y=-8(3)x | | n÷(-8)=15 | | -28+x=-3x+52 | | -2(v+2)+1=-3(3v-1)+1 | | 8a=35^2-27^2 | | 4x^{2}+25=75 | | 13x-8x-2=8 | | 4x+(3-x)-2(5-2x)=14 | | -25+5v=2(1-4v)-5 | | 7w-6=3(w×6) | | x−50=7(2x+3)−6 | | 11x-19x=16 | | 3m+3=m-11 | | x+4+4x+1=49 | | -4b=-244 | | 22=7+14x | | 0=-0.08x^2+106x-9750 | | 0=-0.08x^2+106-9750 | | (x^2-9x-21)=0 | | (3x)-74=(-7x)+66 | | 3x-74=-7x+66 | | 100(4,38x-3,1)=100(1,63x-8,6) |